Further characterization of the recipient ability of Escherichia coli K-12 bacteriophage-resistant mutants. - Manning, P A (1977)
We extended the study of Escherichia coli mutants defective in conjugation and showed that the mutants with altered lipopolysaccharide, which are defective as recipients with F-like donors, are also defective with the I-like plasmid R64-11. However, the extent of reduction in recipient ability for I-like donors does not correlate either with the effect on recipient ability for F-like donors or with the degree of alteration to the lipopolysaccharide.